Pembesaran Ikan Nila (Oreochromis niloticus) pada Budidaya Sistem Resirkulasi Menggunakan Filtrasi Tanaman Hydrilla verticillata dan Ceratophyllum demersum - Bayu Pranata; Aradea Bujana Kusuma (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
This study combined Hydrilla verticillata with Ceratophyllum demersum as a filter in the recirculation system of Tilapia aquaculture. The research objective was to determine the growth rate of tilapia in the recirculation system culture. The filtration used in the recirculation system was H. verticillata and C. demersum. The research method used a completely randomized design (CRD). The parameters observed were fish survival, absolute growth, specific growth rate (SGR), Feed Conversion Ratio (FCR) and water quality. The survival of the fish survived the maintenance of 100%. Individual absolute weight growth ranged from 8.76 to 16.6 g / week. The specific growth rates of tilapia ranged from 2.74 to 4.49%. The FCR value is very good, namely 1.2 and the average temperature, pH and DO values ​​are still in the proper range for the growth of tilapia. During maintenance, only one water change is carried out. Cultivation of the recirculation system is very effective and efficient to apply, especially in areas with limited water availability.